2016
DOI: 10.7863/ultra.15.09023
|View full text |Cite
|
Sign up to set email alerts
|

Expected Sonographic Appearance of the Spleen in Children and Young Adults With Sickle Cell Disease

Abstract: Twenty years ago, children with HbSS SCD were expected to have autosplenectomy by age 5 years. There have been changes in the radiologic appearance of the spleen in patients with SDC, likely due to improved supportive care and the use of acute and chronic transfusion therapy. We found that autosplenectomy is rare by age 5 years, and during childhood and adolescence, the spleen typically appears echogenic, heterogeneous, or both, depending on disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
3
11
4
Order By: Relevance
“…In these studies, the authors suggested a correlation between loss of splenic tissue and low IgM concentration [10]. Surprisingly, although loss of splenic function occurs later in life and to a lesser extent in HbSC than HbSS [5,6], we found no significant difference in IgM level between the two sickle subtype groups. Moreover, therapeutic intensification (by TP or HU) did not prevent decreased IgM level.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…In these studies, the authors suggested a correlation between loss of splenic tissue and low IgM concentration [10]. Surprisingly, although loss of splenic function occurs later in life and to a lesser extent in HbSC than HbSS [5,6], we found no significant difference in IgM level between the two sickle subtype groups. Moreover, therapeutic intensification (by TP or HU) did not prevent decreased IgM level.…”
Section: Discussioncontrasting
confidence: 65%
“…Another study, investigating the mechanical filtration ability of the spleen by using 99 m Tc heated RBC scintigraphy in a cohort of 57 infants with sickle cell anemia, showed that in 32% and 50% of infants, splenic function was decreased at 6 and 18 months of age, respectively [3]. The age varies for irreversible fibrosis of the spleen (a loss also referred to as autosplenectomy), and changes have been described over time, likely due to improved supportive care and the use of acute and chronic transfusion therapy [5]. On ultrasonography, autosplenectomy was found in 39.5% of a cohort of 86 patients with HbSS who were 0–21 years of age but in only 5% of children less than 5 years of age [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations